2021
DOI: 10.1038/s41598-021-86500-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of viremia on organ failure, biomarkers and mortality in a Swedish cohort of critically ill COVID-19 patients

Abstract: The spread of virus via the blood stream has been suggested to contribute to extra-pulmonary organ failure in Coronavirus disease 2019 (COVID-19). We assessed SARS-CoV-2 RNAemia (RNAemia) and the association between RNAemia and inflammation, organ failure and mortality in critically ill COVID-19 patients. We included all patients with PCR verified COVID-19 and consent admitted to ICU. SARS-CoV-2 RNA copies above 1000/ml measured by PCR in plasma was defined as RNAemia and used as surrogate for viremia. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Post-mortem studies have demonstrated viral dissemination and seeding of organs including the bone marrow, heart, and gastrointestinal tract (21). In a Swedish cohort of critically ill COVID-19 patients, the presence of viremia was associated with the need for renal replacement therapy and poor clinical outcome (22).…”
Section: Discussionmentioning
confidence: 99%
“…Post-mortem studies have demonstrated viral dissemination and seeding of organs including the bone marrow, heart, and gastrointestinal tract (21). In a Swedish cohort of critically ill COVID-19 patients, the presence of viremia was associated with the need for renal replacement therapy and poor clinical outcome (22).…”
Section: Discussionmentioning
confidence: 99%
“…Urine N-Ag levels were higher when the Lactate dehydrogenase (LDH) level was elevated. We did not observe an association between N-Ag levels and low platelet counts (<200/µL), abnormal troponin levels (>60 mg/mL), high Ddimer levels (> 1200 mg/mL), or the glomerular Filtration Rate (GFR) based on the (20).…”
Section: Relationship Of Urine and Blood N-ag Levels With Biological Markers Of Covid-19 Severitymentioning
confidence: 55%
“…Blood SARS-CoV-2 RNA is more frequently detectable and found at higher levels in severe forms of Covid-19 (18) (19). SARS-CoV-2 viremia is associated with disease severity, patient outcome and inflammatory biomarkers (20). Ciliated and AT2 cells in airway and alveolar regions are the first targets of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Viremia and extra-pulmonary organ infection with subsequent inflammatory responses in these organs could thus be another explanation for increased systemic neutrophil activity. As previously demonstrated, viral plasma load is associated with critical disease and neutrophil activation [ 34 , 35 ]. In the previously mentioned post-mortem study, SARS-CoV-2 was found in organs distant from the lungs.…”
Section: Discussionmentioning
confidence: 83%